Systematic Mapping Study: Corporate Entrepreneur in Family Firm - Arif Hernowo; Margo Purnomo; Erna Maulina (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: In the growth of family companies, corporate entrepreneurship is very important for the sustainability of family companies that are managed across generations. Sustainability of family companies is more successful in implementing corporate entrepreneurship than other companies. Therefore, researchers study the influence of families on corporate entrepreneurship. This study examines why some families are better at encouraging corporate entrepreneurship in their companies than others. Design/methodology/approach: The method used in this study uses a qualitative method using a study library. A search was conducted on the Scopus database of 33 articles in publications 2005-2021 published in scientific journals included in the inclusion criteria. Findings: The results of this Systematic Mapping study can provide an overview of opportunities to explore new topics on mapping corporate entrepreneurship in family businesses. The most discussed topics are HR, strategy and organizational culture in the general industry and manufacturing sectors. Research limitations/implications: This research is limited to using only one Scopus database. Practical implications: The implications of the research from a practical point of view are how this research data can be better managed in the future by researchers and professionals engaged in entrepreneurship and family businesses. Originality/value: This paper provides a clear description of the role of corporate entrepreneurship in family businesses. This brings together and maps for the first time in an integrated manner several topics related to corporate entrepreneurship in family businesses. This leads to the conclusion that topics related to corporate entrepreneurship in successful family businesses refer to the relationship between human resource management and organizational culture Paper type: Literature review